ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA PADA PENYELESAIAN SOAL CERITA MATEMATIKA MATERI GEOMETRI UNTUK SISWA KELAS V SD NEGERI 52 PANGKALPINANG - Warisa; Maulina Hendrik; Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematical critical thinking ability refers to the way students think in order toanalyze problems systematically and clearly, distinguish problems carefully, andidentify and understand the necessary information to plan appropriate strategies forsolving them. The study aimed to look at how well students can use their criticalthinking skills when solving math word problems related to geometry in the fifthgrade of SD Negeri 52 Pangkalpinang. This study used a qualitative descriptivemethod. Information was gathered using interviews, watching what happened,giving tests, and keeping records. The data were analyzed using a qualitativedescriptive approach proposed by Miles and Huberman, which involves three steps:data reduction, data presentation, and conclusion drawing or verification. Tostrengthen the credibility of the results, triangulation of methods and data sourceswas applied. The findings indicate that students' ability to think critically inmathematics reached 71.43%. A total of 71.43% of students were able to interpretproblems correctly, 53.57% could construct mathematical models, 35.71% wereable to apply calculation strategies and solve problems accurately, and only 21.43%could draw correct conclusions. Therefore, it can be concluded that most studentsare still in the low category in mathematical critical thinking skills.